Sosialisasi Penerapan Pembelajaran Berbasis TPACK pada Guru PPKn Madrasah Tsanawiyah se Kota Mataram - Mohammad Ismail; Edy Herianto; Lalu Sumardi; Basariah (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The purpose of this service is to improve the competence of teachers in partner schools regarding the concept of TPACK-based learning. In addition, teachers have the competence to design and implement TPACK-based learning so that they can achieve learning objectives holistically. The solution offered in this service is to carry out a series of socialization activities and training on the application of TPACK-based learning. This socialization activity will be attended by 20 PPKn teachers in Madrasah Tsanawiyah in Mataram City as participants. The results of the socialization showed that participants related to understanding about TPACK increased to 62.5% answered that they had understood about TPACK. Participants' perceptions of the use of technology in Civics learning increased to 100% which stated that Civics learning must use technology. The use of TPACK in learning increased to 70%, because previously participants did not understand what TPACK was and its application in learning. This is directly proportional to the selection of materials that are adapted to the use of learning technology in the classroom which also increases to 65%. Likewise, the evaluation by utilizing technology also increased to 80%. Based on this, the implementation of the service is said to be successful.